How best to open up local democracy? A randomised experiment to encourage contested elections and greater representativeness in English parish councils. Issue 6 (2nd November 2018) - Ryan, Matt; Stoker, Gerry; John, Peter; Moseley, Alice; James, Oliver; Richardson, Liz; Vannoni, Matia
ABSTRACT: Interventions aimed at increasing the supply and representativeness of elected officials range from facilitative to the formally authorised. This paper reports on a field experiment aimed at testing the effect of facilitative approaches at the local level based on a collaboration between parish councils and the research team. We randomly allocated 818 parish council clerks across five counties in Southern England, either to receive information and the opportunity for member training for recruitment, or not to receive this contact. We investigated the effect of this intervention on political recruitment. Despite evidence of an effect on use of social media, our results suggest that there are significant institutional and structural barriers to participation in local politics that cannot easily be overcome using facilitative measures.